Baseline Study of Sputum Microscopy for Diagnosis of Tuberculosis in Western Region of Nepal - Dhakal, Amrita; Nepal, Samata; Atreya, Alok; Rijal, Basista (Medical Journal of Shree Birendra Hospital, 2018)
Introduction: Tuberculosis is a major health issue in Nepal. Early detection of tuberculosis is essential to identify the case which limits the transmission of tuberculosis and builds an effective approach of tuberculosis control policy. Therefore, the present study is aimed to assess the case of tuberculosis by sputum smear examination. Methods: A prospective study was conducted in a tertiary care hospital of Western Nepal. Two sputum samples were collected from each suspect – spot specimen on the first day and one early morning specimen on the second day. The standard protocol of Ziehl Neelsen stain was applied to detect the acid fast bacilli. Results: Out of 280 smears from suspected patients, only 30 showed smear positivity (10.7%). Among the total identified positive case of tuberculosis (30/280), the highest rate was observed in the age group of 56-65 years. Males (56.7%) were highly affected by tuberculosis than females (43.3%). The minimum age of the suspects was two years and maximum age was of 105 years with mean age of 53.6 years. Conclusions: It is concluded that prevalence of tuberculosis is high in patients attending tertiary care hospital in Western region of Nepal, which is slightly higher than the annual report of National Tuberculosis Program 2017. Incidence of pulmonary tuberculosis is higher in males as compared to females.